The Role of Zakat in Poverty Alleviation: A Study of the Impact of Zakat and the CIBEST Welfare Index - Nurzidta Okta Rinanda; Bhimo Rizky Samudro; Mulyanto Mulyanto; Budi Kusumo Palgunadi Wibowo (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2025)
This study aims to identify and analyze the role of zakat in poverty alleviation in Indonesia, focusing on the impact of zakat as measured by the Zakat Impact Assessment (KDZ) and the CIBEST Welfare Index. Using a quantitative descriptive analysis method with an ANCOVA approach, this study examines the relationship between these variables in the period 2018-2022. The results of the analysis indicate that zakat plays a significant role in poverty reduction and welfare improvement, with a greater impact in areas with higher welfare. However, the COVID-19 pandemic has had a significant negative impact on the effectiveness of zakat distribution, as reflected in a decrease in the KDZ level. The average KDZ during the study period was 0.503 and the average CIBEST was 0.297. Two-Way ANOVA analysis showed that the CIBEST variable significantly influenced KDZ (F = 4.273, p < 0.001), with a large impact (η² = 0.558), while the COVID-19 pandemic had a significant effect with a moderate impact (η² = 0.128). This study suggests that to increase the impact of zakat, there needs to be stronger synergy between zakat institutions, the government, and the community as well as the integration of zakat into broader development policies, especially in areas with high poverty rates.